CD200-based cell sorting results in homogeneous transplantable striatal neuroblasts for human cell therapy for Huntington's disease - Francisco J. Molina-Ruiz; Phil Sanders; Cinta Gomis; Jordi Abante; Francisco Londoño; Georgina Bombau; Mireia Galofré; Gal la Vinyes-Bassols; Veronica Monforte; Josep M. Canals (Neurobiology of Disease)
Neurodegenerative diseases are characterized by selective loss of neurons. Cell replacement therapies are the most promising therapeutic strategies to restore the neuronal functions lost during these neurodegenerative processes. However, cell replacement-based clinical trials for Huntington's (HD) and Parkinson's diseases (PD) failed due to the large heterogeneity of the samples.Here, we identify CD200 as a cell surface marker for human striatal neuroblasts (NBs) using massively parallel single-cell RNA sequencing. Next, we set up a CD200-based immunomagnetic sorting pipeline that allows high-yield enrichment of human striatal NBs from in vitro differentiation of human pluripotent stem cells (hPSCs). We also show that sorted CD200-positive cells are striatal projection neuron (SPN)-committed NBs which survive upon intra-striatal transplantation in adult mice with no evidence of graft overgrowth in vivo.In conclusion, we implemented a new CD200 cell selection strategy that reduces the heterogeneity and batch-to-batch variation and potentially decreases the teratogenic risk of hPSC-based cell therapy for neurodegenerative diseases.